Soil Pollution and Plant Efficiency Indices for Phytoremediation of Heavy Metal(loid)s: Two-Decade Study (2002–2021) - Adarsh Kumar; Tripti; Deep Raj; Subodh Kumar Maiti; Maria Maleva; Galina Borisova (Metals, 2022)
This paper reviews research on phytoremediation (2002–2021), particularly for the estimation of plant efficiency and soil pollution indices, examining the extraction of metals from soil and plants growing under both artificial (spiked with specific metal) and natural conditions. From the analysis of >200 published experimental results, it was found that contamination factor and geo-accumulation index as well as translocation and bioconcentration factors are the most important soil pollution and plant efficiency metrices, respectively, which are gaining importance to assess the level of metal pollution and its transfer from soil to plant to find a better metal clean-up strategy for phytoremediation. To access the metal concentration, it was found that the most widely accepted extractants to dissolve and extract the metals from the soil and plant were HNO3 and HClO4 (mainly in 5:1; v/v or 4:1; v/v), which are used both in natural and artificial metal contamination studies. Moreover, plants such as Pteris vittata, Monochoria korsakowi, Lolium perenne, Festuca rubra, Poa pratensis, Ricinus communis, and Siegesbeckia orientalis can act as hyperaccumulators under both natural and artificial experiments and can be directly implemented into the fields without checking their further efficiency in phytoremediation.